The Relationship Between Modified Rodnan Skin Score (mRSS) With Pulmonal Hypertension and Lung Fibrosis in Systemic Sclerosis Patients - Syaifur Rohman; Rakhma Yanti Hellmi; Friska Anggraini HS (Indonesian Journal of Rheumatology, 2021)
Background: Systemic sclerosis (SSc) is a connective tissue disease, which affects the skin, blood vessels, heart, lungs, kidneys, gastrointestinal tract and musculoskeletal system. The manifestations in blood vessels include pulmonary hypertension which can be seen from echocardiography, while the manifestations to the lungs in the form of pulmonary fibrosis are examined by high-resolution computed tomography (HRCT). Modified Rodnan Skin Score (mRSS) a method for measuring skin thickness in SSc patients. Objective: This study aims to determine the relationship between mRSS and pulmonary hypertension and pulmonary fibrosis in SSc patients. Methods and Materials: Research with a cross sectional approach at Dr Kariadi Hospital. There were 23 study subjects with SSc patients having their mRSS measured by a rheumatologist and an HRCT examination by a radiologist to see the percent of lung damage and echocardiographic examination by a cardiologist to measure the Tricuspid Regurgitation Velocity Maximum (TRV Max) as a marker of pulmonary hypertension. Normality test using Saphiro-Wilk. The Spearman rank correlation test was used to analyze the relationship between the mRSS score, pulmonary hypertension and pulmonary fibrosis. Results: The proportion of study subjects with a mean age of 40.39 years, women, and 4.43 years of illness. The mean mRSS score was 17.43. Examination of pulmonary hypertension from echocardiography found most of the light category 95.6%, heavy category 4.4%, while the HRCT examination found pulmonary fibrosis of 86.9%, normal 13.1%. There are significant relationship between mRSS and pulmonary fibrosis (r = 0.485, p = 0.019), and significant relationship between pulmonary hypertension (r = 0.63, p = 0.001) Conclusion: There is a significant relationship between mRSS, pulmonary fibrosis and pulmonary hypertension.